LANGUAGE POLICY AND MANAGEMENT CLASS FORMATION IN THE KAZAKH AUTONOMOUS SOVIET SOCIALIST REPUBLIC. 1920-1936 YEARS - D., Amanzholova (Journal of history, 2018)
The issue of language was determined not only by the choice of optimal communication tool and modernization of multi-ethnic population, but had a deep symbolic and political significance. Language was an important tool for shaping peoples ethnoidentity of the USSR, served in the republics as marker for the admission to the privileges of the titular ethnic group and consolidate its administrative-territorial status. In the organization and provision of the all government system of governance in the KASSR in 1920-1936 years special role played in the dynamics of discursive practices in bilingual space. The functioning of Russian and Kazakh languages has an ambivalent impact on the formation and activities of the management class in the indigenization and the transformation of Kazakh alphabet from Arabic script to Latin and Cyrillic.